Rapid Review of The Literature on Nursing Students’ Perception and Experience During COVID-19 Pandemic - Nishara, M.G.S.; Herath, H.M.H.I.; Shavindi, J.M.L.; P.P.M. Lakrandi, P.P.M.; Thavalingaratinam, P.; Asurakkody, T.A. (My University, 2021)
Introduction: COVID-19 pandemic driven the world to a global emergency and fighting against the pandemic made an overwhelming demand for the health sector. As numerous impacts of the crisis, nursing students tried to view, justify and adapt to the pandemic on their perception. Objective: To identify and synthesize available evidence on the nursing students’ perceptions and experiences regarding the COVID-19 pandemic. Methods: Rapid literature review was performed from 18th to 21st June 2021 on four databases; Google Scholar, Science Direct, PubMed, and Web of Science to identify the publications between 2019 and 2021. Findings were categorized under the five levels of Bronfenbrenner’s ecological model. Results: Thirty-five articles were eligible from the initial search strategy of 1076 studies. Of these, the USA has the highest contribution (17.14%). Upon the organization of evidence into levels, major and subcategories; intrapersonal level included knowledge (COVID-19), health distress (anxiety, nervousness, fear, physical discomfort), experiences (clinical, online learning), skills (confidence), and attitudes (pride of profession). Family burden and teamwork were categorized under the interpersonal level. The institutional level consisted of classroom and clinical learning. Social relationships and policy development subsisted under the community and public policy levels respectively. Findings revealed that positive experience ([40%] confidence, pride of the profession) strengthens as frontline health care workers. Negative experiences ([77.14%] increased anxiety, physical discomfort, isolation, and fear of descendants’ contamination) have adversely affected. Reformation of academics to online and continuing clinical learning were devastating factors during the pandemic. Conclusions: Nursing students have both positive and negative perceptions and experiences towards the COVID-19 pandemic. University administration, Deans, Department heads had gained a chance to prepare an advanced crisis plan that could be rapidly and effectively implemented, considering new trends in nursing education. Further, enhance knowledge on pandemics and computer literacy among nursing students are vital mechanisms during a pandemic.

Introduction: COVID-19 pandemic driven the world to a global emergency and fighting against the pandemic made an overwhelming demand for the health sector. As numerous impacts of the crisis, nursing students tried to view, justify and adapt to the pandemic on their perception. Objective: To identify and synthesize available evidence on the nursing students’ perceptions and experiences regarding the COVID-19 pandemic. Methods: Rapid literature review was performed from 18th to 21st June 2021 on four databases; Google Scholar, Science Direct, PubMed, and Web of Science to identify the publications between 2019 and 2021. Findings were categorized under the five levels of Bronfenbrenner’s ecological model. Results: Thirty-five articles were eligible from the initial search strategy of 1076 studies. Of these, the USA has the highest contribution (17.14%). Upon the organization of evidence into levels, major and subcategories; intrapersonal level included knowledge (COVID-19), health distress (anxiety, nervousness, fear, physical discomfort), experiences (clinical, online learning), skills (confidence), and attitudes (pride of profession). Family burden and teamwork were categorized under the interpersonal level. The institutional level consisted of classroom and clinical learning. Social relationships and policy development subsisted under the community and public policy levels respectively. Findings revealed that positive experience ([40%] confidence, pride of the profession) strengthens as frontline health care workers. Negative experiences ([77.14%] increased anxiety, physical discomfort, isolation, and fear of descendants’ contamination) have adversely affected. Reformation of academics to online and continuing clinical learning were devastating factors during the pandemic. Conclusions: Nursing students have both positive and negative perceptions and experiences towards the COVID-19 pandemic. University administration, Deans, Department heads had gained a chance to prepare an advanced crisis plan that could be rapidly and effectively implemented, considering new trends in nursing education. Further, enhance knowledge on pandemics and computer literacy among nursing students are vital mechanisms during a pandemic
Keywords: Nursing students; Education; Perceptions; Experiences; COVID-19 pandemic